2018
DOI: 10.1007/s00784-017-2323-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cell survival and heat shock protein expression after radiation in normal dermal fibroblasts, microvascular endothelial cells, and different head and neck squamous carcinoma cell lines

Abstract: HNSCC use HSP to escape radiation-induced apoptosis and certain subtypes might increase proliferation after low-dose irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…We found that cell death in the two cell types mainly occurred after 5 Gy irradiation, with TICAE cells responding with Annexin V and Caspase 3/7 elevation while TIME cells responded with Annexin V elevation and membrane leakage as indicated by cellular dextran fluorescein positivity. The absence of Caspase 3/7 elevation in TIME cells confirms the findings in primary human microvascular endothelial cells exposed to X-rays in the 2 to 12 Gy dose range (Muschter et al, 2018). Overall, the cell death observed in our study is in line with previous findings in umbilical vein endothelial cells (Rombouts et al, 2013) and microvascular endothelial cells (Langley et al, 1997;Rousseau et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…We found that cell death in the two cell types mainly occurred after 5 Gy irradiation, with TICAE cells responding with Annexin V and Caspase 3/7 elevation while TIME cells responded with Annexin V elevation and membrane leakage as indicated by cellular dextran fluorescein positivity. The absence of Caspase 3/7 elevation in TIME cells confirms the findings in primary human microvascular endothelial cells exposed to X-rays in the 2 to 12 Gy dose range (Muschter et al, 2018). Overall, the cell death observed in our study is in line with previous findings in umbilical vein endothelial cells (Rombouts et al, 2013) and microvascular endothelial cells (Langley et al, 1997;Rousseau et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…HSP27 can also mediate the effects of certain therapeutic approaches. RT increased levels of HSP27 and p-HSP27 in head and neck cancer cell lines [28], and in mouse lung in vivo [29]. Pavan and colleagues [30] found that HSP27 was required for spontaneous lung metastasis in a mouse model of ovarian cancer and inhibition of HSP27 has been shown to sensitize tumors to chemotherapy [30] and RT [31].…”
Section: Introductionmentioning
confidence: 99%
“…Later, cells with similar properties were shown to reside in various tissues and organs, such as adipose tissue, umbilical cord matrix, synovial membrane, and dental tissues . A major advantage of the isolation of mesenchymal stem cells from adipose tissue is the uncomplicated acquisition of cells by liposuction or resection from subcutaneous fat tissue . Fat-derived mesenchymal stem cells are termed adipose-derived mesenchymal stem cells (ASCs) and can be expanded from liposuction material .…”
Section: Introductionmentioning
confidence: 99%
“…The volumes of lipoaspirate that are needed for procedures like vocal fold augmentation typically amount to a few milliliters. 12 This information highlights the need for new minimally invasive fat harvesting techniques. However, important factors for the clinical outcome include the amount and viability of ASCs as well as their secretory activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation